Mimicry and Hybridity as Forms of Resistance in the Novel Cantik itu Luka by Eka Kurniawan - Aulia Rosyada, Sabila; Supriyanto, Teguh; Doyin, Mukh (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The novel "Cantik itu Luka" represents colonial events with lasting impacts on Eastern societies. In response to colonization, Eastern nations endeavored to resist through acts of mimicry and hybridity. This research aims to analyze mimicry and hybridity as forms of resistance in Eka Kurniawan's novel "Cantik itu Luka." The study seeks to broaden societal awareness regarding postcolonial studies, particularly focusing on forms of resistance, especially mimicry and hybridity. The research employs a literary sociology approach with a qualitative research design. The primary data source is the text of "Cantik itu Luka" by Eka Kurniawan. Data in this study consist of excerpts from the novel suspected to contain forms of resistance in terms of mimicry and hybridity. Data collection utilizes heuristic techniques, while data analysis employs hermeneutic techniques. The findings of this research reveal the presence of resistance exhibited by characters Dewi Ayu and indigenous characters through mimicry as a form of opposition. Imitation is observed in terms of thought patterns, education, language, and lifestyle. Additionally, indigenous characters demonstrate another form of resistance through hybridity, manifested in behavior, living tools, mindset, lifestyle, and clothing styles—an effort to preserve identities eroded by colonization.